Transformation of urban tissue along downtown arteries Morphometric evaluation of resilient urban form - Kowalski Kamil; Hanzl Małgorzata (Lodz University of Technology Press, 2023)
The complexity of urban processes, which occurred in post-socialist countries after the second world war, contributed to the creation of underdeveloped urban tissue that was, in many cases, resistant to changes. This applies particularly to cities that grew rapidly, such as Lodz. Unfinished processes of transforming urban tissue along urban arteries are still an unsolved problem of the city centre of Lodz. This article aims to compare and evaluate resilience of urban tissue that have taken place over the years along newly built urban arteries. The research contributes to the methodology of urban morphometry. We consider the construction of the most important transportation routes in Lodz as representative example. Based on the measurements of urban tissue elements, we assessed the dynamics of the changes taking place in the spatial structure along the main urban arteries. Besides, the aggregated data enabled us to reflect on the reasons for the transformations and their context. This study is in line with the current trend of searching methods supporting the evaluation of resilient urban form. In addition, the article continues the research initiated by Professor Marek Koter, whose study was a pioneering Polish solution in the implementation of quantitative methods to assess the transformation of the urban tissue.
Keywords: urban morphometry; urban resilience; streets; arteries; urban form; morfometria miasta; odporność miasta; ulice; arterie; forma urbanistyczna